2021
DOI: 10.3390/app11073178
|View full text |Cite
|
Sign up to set email alerts
|

LDM-Ex-FDM: A Novel Multi-Service Transmission Scheme for the ATSC 3.0 System

Abstract: In order to improve system coverage performance, in this paper, a multi-service transmission scheme on the basis of the puncturing technique, namely layered division multiplexing extension frequency-division multiplexing (LDM-Ex-FDM), is proposed. The key idea of the proposed scheme is that the symbols punctured from the enhanced layer (EL) of fixed services will be independently transmitted on a certain number of subcarriers orthogonal to the LDM signal of the core layer (CL) and most of the EL. By doing so, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The success of iterative decoding depends on the labeling map (or simply, labeling) used to map binary blocks (i.e., parts of the codeword) onto the constellation points. Gray labeling, which is widely used in current wireless systems that employ original BICM, such as WLAN [ 1 , 2 ] and digital terrestrial television broadcasting [ 3 , 4 ], has been shown to be the worst choice from the perspective of iterative decoding goals. The optimal labeling maps for BICM-ID have been investigated in many papers, e.g., [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The success of iterative decoding depends on the labeling map (or simply, labeling) used to map binary blocks (i.e., parts of the codeword) onto the constellation points. Gray labeling, which is widely used in current wireless systems that employ original BICM, such as WLAN [ 1 , 2 ] and digital terrestrial television broadcasting [ 3 , 4 ], has been shown to be the worst choice from the perspective of iterative decoding goals. The optimal labeling maps for BICM-ID have been investigated in many papers, e.g., [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Layer division multiplexing (LDM) [1], a power-based non-orthogonal multiple access (NOMA) technology, is gaining popularity in a variety of wireless applications to deliver robust high-definition services [2][3][4]. Recently, the advanced television systems committee (ATSC) 3.0 standard applied LDM for broadcasting systems [5][6][7][8][9][10]. It allows for a high-capacity link for stationary users as well as a robust configuration for mobile users.…”
Section: Introductionmentioning
confidence: 99%